2011
DOI: 10.1002/macp.201000638
|View full text |Cite
|
Sign up to set email alerts
|

Use of Reactive and Functional Hydrophobes (Hydrophobins) in the Miniemulsion Polymerization of Styrene and Methyl Methacrylate

Abstract: The successful use of multitasking polycaprolactone‐based hydrophobins for miniemulsion polymerization of model monomers like styrene and methyl methacrylate is demonstrated. These hydrophobins were synthesized in two steps – the synthesis of polyester diol (i.e., polycaprolactone diol) followed by polycondensation with an equimolar amount of azobis(cyanopentanoic acid dichloride). The hydrophobin, besides acting as a hydrophobe and initiator for the miniemulsion polymerization, also provided functionality; in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These motifs are, however, well-known to dissociate upon heating, exposure to light, and ultrasonication and have previously been incorporated into various polymers. The latter were used as radical macroinitiators for the synthesis of well-defined block copolymers, the fabrication of cross-linked PMMA microspheres, and the release of molecules grafted onto nanoparticles in imaging or delivery applications. , It was also shown that the azo-motif can be used to create mechanoresponsive materials that can be degraded upon ultrasonication in solution . We show here that polyamides and polyurethanes comprising 4,4′-azobis­(4-cyanovaleric acid) or 2,2′-azobis­[2-methyl- N -(2-hydroxyethyl)­propionamide] residues in the backbone display mechanical characteristics that are virtually identical to those of the azo-free reference materials; however, these materials can be degraded “on command” upon heating or exposure to (ultraviolet) light.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…These motifs are, however, well-known to dissociate upon heating, exposure to light, and ultrasonication and have previously been incorporated into various polymers. The latter were used as radical macroinitiators for the synthesis of well-defined block copolymers, the fabrication of cross-linked PMMA microspheres, and the release of molecules grafted onto nanoparticles in imaging or delivery applications. , It was also shown that the azo-motif can be used to create mechanoresponsive materials that can be degraded upon ultrasonication in solution . We show here that polyamides and polyurethanes comprising 4,4′-azobis­(4-cyanovaleric acid) or 2,2′-azobis­[2-methyl- N -(2-hydroxyethyl)­propionamide] residues in the backbone display mechanical characteristics that are virtually identical to those of the azo-free reference materials; however, these materials can be degraded “on command” upon heating or exposure to (ultraviolet) light.…”
Section: Introductionmentioning
confidence: 95%
“…These motifs are however well known to dissociate upon heating, exposure to light, and ultrasonication, and have previously been incorporated into various polymers. The latter were used as radical macroinitiators for the synthesis of well-defined block copolymers, [14][15][16][17][18][19][20][21] the fabrication of crosslinked PMMA microspheres, 22 and for the release of molecules grafted onto nanoparticles in imaging or delivery applications. 23,24 It was also shown that the azo-motif can be used to create mechanoresponsive materials that can be degraded upon ultrasonication in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the single functional group being introduced by the initiator, the target molecule would be accessible by application of a polystyrene macroinitiator with methylcoumarin end groups. This novel macroinitiator would be accessible by dimerization of α ‐methylcoumarin‐ ω ‐amino‐polystyrene with 4,4′‐azobis‐4‐ cyanopentanoyl chloride (ACPC) 8…”
Section: Resultsmentioning
confidence: 99%